PENGARUH TINGKAT BAGI HASIL, TINGKAT SUKU BUNGA, JUMLAH KANTOR, DAN UKURAN BANK TERHADAP JUMLAH DEPOSITO MUDHARABAH PADA PERBANKAN SYARIAH - Abdaliah Abdaliah; Adhisyahfitri Evalina Ikhsan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
This research is empirical, where the purpose of this study was to test the effect of profit sharing rate, interest rate, number of offices, and the size of the bank together against mudharabah deposits in Islamic Banking, and then test the effect of profit sharing rate to deposits mudaraba, the effect level interest rate on deposits mudaraba, the influence of the number of offices to deposit profit and influence the size of the bank to deposit mudharabah on Islamic Banking. The population used in this study are listed in Islamic banks during out 2011 to 2014. The population criteria used in this study are listed in Islamic banks and publish an annual report for the year 2011 to 2014. The population in 2010 was 10, in 2012 a total of 11, in 2013 a total of 11, and in 2014 a total of 11, thus the number of observations in this study for 5 years is as much as 54 observation. The equipment used in this research is multiple linear regression. The results of this study explains that the profit sharing rate, the interest rate, the number of banks and bank size jointly affect the amount of deposits in Islamic banking mudharabah. Then the results also prove that the rate of profit sharing effect on the amount of deposits mudaraba in the Islamic banking, the interest rate does not affect the amount of deposits mudaraba in the Islamic banking, the number of banks affect the amount of deposits mudaraba in the Islamic banking and bank size does not affect the amount of deposits mudaraba on islamic banking.